Eficácia e efetividade do crizotinibe no tratamento de primeira linha de câncer de pulmão de células não pequenas com mutação da quinase do linfoma anaplásico - Barbara Delano Cruz (2020)
In 2018, 18.1 million new cases of malignant neoplasms were diagnosed worldwide, and Lung Cancer (LC) was the most incident type (11.6% of the total cases) and the main cause of death (18,4% of total cancer deaths) when considering both sexes. However, LC is not a single disease, as it has important histological and genetic variations. It is currently divided into two main types: NonSmall Cell Lung Cancer (NSCLC) (80%) and Small Cell Lung Cancer (SCLC) (20%). Although there are still late diagnoses and a high mortality rate for LC in general, it is worth noting that the NSCLC is showing rapid evolution in the treatment arsenal, bringing better expectations of prognosis as new target therapies and monoclonal antibodies, aimed at modulation of the immune system, are being developed and made available. One of the most recent discoveries in the context of NSCLC disease, which occurred in 2007, was the mutation of the Anaplastic Lymphoma Kinase receptor (ALK). However, its frequency is considered low, being found in only 2 % to 5% of NSCLC diagnosed the high number of patients with lung cancer make this an important genetic change. And for its treatment, the drug crizotinib was developed, it´s a targetdirected therapy, and considered a first generation inhibitor. Methodology: Conducting a systematic review with meta-analysis of Randomized Clinical Trials (RCT) and observational cohort studies published in the main electronic databases (Cochrane Library, EMBASE, LILACS and PUBMED), with the outcome analyzed: Global Survival (OS), Progression-Free Survival (PFS). Results: Of 2,504 publications identified in the literature, 8 publications from 7 studies were selected, 2 of which were RCTs and 5 related to cohort. In the meta-analyzes carried out, high heterogeneity was identified between the studies, with a significant PFS gain of HR 0,38; IC 95%: 0,30 – 0,49; p < 0,00001, not showing, however, a statistically significant gain in OS, HR 0,68; IC 95%: 0,43 – 1,08; p = 0,10. Conclusion: It is possible that in patients with NSCLC with a positive profile for the ALK gene mutation, there is an increase in PFS when treated with crizotinib compared to conventional chemotherapy, with no increase in overall survival. However, the effectiveness and safety of crizotinib in patients with NSCLC, positive ALK, needs confirmation of the initial results, in a study design preferably masked and respecting the initial randomization. Furthermore, the identification of the genomic profile of patients with NSCLC can indicate an algorithm of treatment alternatives, in which not only a sequence of personalized therapies and/ or combination of drugs is administered, but it can also form a precedent for transforming the NSCLC ALK + into a chronic disease rather than fatal one.